2022
DOI: 10.3847/1538-3881/ac53a7
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Companions to TESS Objects of Interest: A Test of Planet–Companion Alignment

Abstract: We present a catalog of stellar companions to host stars of Transiting Exoplanet Survey Satellite Objects of Interest (TOIs) identified from a marginalized likelihood ratio test that incorporates astrometric data from the Gaia Early Data Release 3 catalog (EDR3). The likelihood ratio is computed using a probabilistic model that incorporates parallax and proper-motion covariances and marginalizes the distances and 3D velocities of stars in order to identify comoving stellar pairs. We find 172 comoving companion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 70 publications
(84 reference statements)
0
15
1
Order By: Relevance
“…Indeed, observational studies have shown that the occurrence rate of exoplanets in stellar binaries tends to be smaller than those of wider binaries or single stars (e.g., Wang et al 2014;Kraus et al 2016;Moe & Kratter 2021;Ziegler et al 2021). Moreover, the orbits of planet-hosting stellar binaries appear to be statistically aligned with those of the planets, while orbital inclinations of binaries without planets are likely isotropic (e.g., Behmard et al 2022;Christian et al 2022;Dupuy et al 2022). The orbital alignment between binaries and planets could be primordial if both stellar components and the planets all form within the same massive disk or hierarchical cloud fragmentation that preserves orbital angular momenta (e.g., Sigalotti et al 2018;Tokovinin 2018;Christian et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, observational studies have shown that the occurrence rate of exoplanets in stellar binaries tends to be smaller than those of wider binaries or single stars (e.g., Wang et al 2014;Kraus et al 2016;Moe & Kratter 2021;Ziegler et al 2021). Moreover, the orbits of planet-hosting stellar binaries appear to be statistically aligned with those of the planets, while orbital inclinations of binaries without planets are likely isotropic (e.g., Behmard et al 2022;Christian et al 2022;Dupuy et al 2022). The orbital alignment between binaries and planets could be primordial if both stellar components and the planets all form within the same massive disk or hierarchical cloud fragmentation that preserves orbital angular momenta (e.g., Sigalotti et al 2018;Tokovinin 2018;Christian et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Constraining the barycentric orbit of Kepler-444 BC relative to A provides boundary conditions on the size and mass of the protoplanetary disk that resided around A, informs past and future dynamical interactions between the BC binary and the inner planets, and places this system in the context of statistical studies of planet-hosting stellar binaries (e.g., Behmard et al 2022;Christian et al 2022;Dupuy et al 2022). Dupuy et al (2016) provided the first constraints of Kepler-444 BC's barycentric orbit by combining A's multiepoch radial velocities (RVs), the relative RV between the BC and A components, and relative astrometry from 3 yr of monitoring using adaptive optics (AO) imaging.…”
Section: Introductionmentioning
confidence: 99%
“…We place a conservative upper limit on the flux ratio of 0.07 for an unresolved stellar companion at separations |Δv| > 5 km s −1 . a (i) high eccentricity or (ii) the outer companion lies on an orbit that is coplanar with the inner transiting system (see Appendix B in Behmard et al 2022). The inferred eccentricity with 1σ uncertainties for the orbit of the white dwarf companion is = -+ e 0.99 0.47 0.01 .…”
Section: Constraints On Resolved Bound Companionsmentioning
confidence: 99%
“…We applied this method to twin wide binaries and showed that they are highly eccentric (Hwang et al 2022a), suggesting that they were formed at smaller separations and their orbits were widened by subsequent interaction with the environments (El-Badry et al 2019). If one of the component star is an eclipsing binary or has a transiting planet, then v-r angles can constrain the orbital alignments between the outer companions and the inner eclipsing or transiting systems (Behmard et al 2022;Cañas et al 2022;Christian et al 2022).…”
Section: Hwangmentioning
confidence: 99%
“…If the inner binary has a nearly edge-on orientation (e.g. eclipsing binaries), then the wide tertiary with an aligned co-planar orbit would have v-r angles close to 0 • or 180 • (Behmard et al 2022). If the orientation of the wide tertiaries is isotropic with respect to the Sun, which can be due to either the isotropic orientation of wide tertiaries with respect to the inner binaries or to the relatively isotropic selection of the inner binaries' orientation (e.g.…”
Section: Completeness Of Nearby Sources Around Gaia Close Binariesmentioning
confidence: 99%